Students opinion about the success of mobile technology in libraries: a case study of Jawaharlal Nehru University (JNU), New Delhi. Issue 9 (29th August 2014) - Kumar, Amit
Abstract : Purpose: Present paper explores the students' opinion of Jawaharlal Nehru University, New Delhi, regarding the use and success of mobile technology in the library environment for providing better services by library and their expectations from the library through mobile technology. Design/methodology/approach: A survey was conducted through a well-structured and precise questionnaire circulated personally among 200 students studying in Jawaharlal Nehru University for the academic session 2012-2013. Findings: The study explores that majority of the students are in favor of using the mobile technology for better services by the libraries and it is expected by the students that services should be provided to them by libraries through mobile technology. Research limitations/implications: The geographical area of study was confined to the students of the JNU, New Delhi only regarding their opinion on use of mobile technology by the library. Originality/value: The paper highlights the students' opinion of JNU regarding the use of mobile technology by the library for better services and further it also explores the expectations of students from the library through this technology.